(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this work, Modal fibers were dyed in supercritical carbon dioxide using C.I.Disperse Yellow 54, and dying process was investigated and optimized. The key parameters including dye dosage, temperature, pressure and time of dyeing process were discussed both theoretically and experimentally. The degree of crystallinity and strength of the fibers were affected by fiber modification and dyeing. The final results obtained from this experiment indicated that only 20min was required to reach the equilibrium condition in supercritical carbon dioxide, and the dye yield increased with the increase in temperature. The dye-uptake increased along with the increase of pressure, however when the pressure was extended up to 18Mpa, the dye-uptake decreased slowly. The optimized conditions include winding of fibers around dyeing axis with the combination of different CO_2 inlets, dyeing temperature at 100°C, pressure at 18MPa and time 20min.